2020
DOI: 10.3390/polym12122934
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Properties of Binary Polyrhodanine Manganese Ferrite Nanohybrids—From the Energy Converters to Biological Activity

Abstract: The PRHD@MnFe2O4 binary hybrids have shown a potential for applications in the biomedical field. The polymer cover/shell provides sufficient surface protection of magnetic nanoparticles against adverse effects on the biological systems, e.g., it protects against Fenton’s reactions and the generation of highly toxic radicals. The heating ability of the PRHD@MnFe2O4 was measured as a laser optical density (LOD) dependence either for powders as well as nanohybrid dispersions. Dry hybrids exposed to the action of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 34 publications
(34 reference statements)
1
22
0
Order By: Relevance
“…A recent study by Zachanowicz et al found that the number of viable bacteria was significantly reduced after exposure to binary polyrhodanine manganese ferrite nanohybrids. This effect was directly related to the amount of nanohybrid polymer content, and the higher the amount, the more antimicrobial effects [ 38 ]. The antibacterial activity of PR/Fe/Go synthesized in kombucha supernatant media showed more potent than their non-bioinorganic synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Zachanowicz et al found that the number of viable bacteria was significantly reduced after exposure to binary polyrhodanine manganese ferrite nanohybrids. This effect was directly related to the amount of nanohybrid polymer content, and the higher the amount, the more antimicrobial effects [ 38 ]. The antibacterial activity of PR/Fe/Go synthesized in kombucha supernatant media showed more potent than their non-bioinorganic synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Since the physicochemical properties of the hybrid materials were already a subject of our recent studies, the reader is strongly encouraged to familiarize themselves with the results presented earlier, where detailed characteristics can be found [ 8 ]. Here we would like to underline that both stocks of nanoparticles and composites are well defined since they are from the same synthetic batch in both articles.…”
Section: Resultsmentioning
confidence: 99%
“…Protocols of the MnFe 2 O 4 nanoparticles and PRHD@MnFe 2 O 4 composites synthesis were described by us in detail elsewhere [ 8 , 10 ]. Metal acetylacetonate complexes were weighted under a protective atmosphere of N 2 (acrylic glovebox P10R250T2, GS Glove Box Systemtechnik GmbH, Malsch, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements of the FTIR-ATR spectra were performed on a Nicolet iZ10 spectrometer (Thermo Fischer Scientific, Waltham, MA, USA) equipped in diamond ATR accessory covering the spectral range between 4000–500 cm −1 at room temperature. Magnetic characterization of the Co 1−x Mn x Fe 2 O 4 colloids was presented by us previously [ 16 ]; thus, the interested reader is advised to follow that article for details. The hybrid particle mean size and distribution were estimated by using free-image processing software ImageJ v.1.46 [ 17 ] through analysis of SEM images by taking into consideration of 100 hybrid particles (longest diameter was measured due to elongated shape of objects).…”
Section: Methodsmentioning
confidence: 99%